Modeling nonlinear waves in graphene - Wei, D.; Elgindi, M.; Hazin, H.; Soukiassian, Y.; Daripa, P. (Nazarbayev University, 2014)
The graphene-based resonator and its application to mass sensing based on nonlinear waves have been poorly studied numerically [1]. The project's main objective is to model and understand how graphene behave in free and forced vibrations and calculate the nonlinear resonance frequencies.
Keywords: nonlinear waves; materials; methods; model